STRATEGI LATECOMER FIRMS DALAM MERAIH DAYA SAING GLOBAL: Studi Kasus Latecomer Firms Teknologi Tinggi Asia - Pratiwi, Cholillah Suci (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2018)
This research is aimed to analyze strategies done by Asian Latecomer Firms (LCF), which work in high technology industry, in order to increase their global competitiveness and how Asian governments assist and enhance their LCFs’ efforts. Asiagoven LCFs have three strategies to transform their firms competitiveness. First, LCFs built linkages with Foreign Multinational Companies (MNC) to gain basic technologies through exploiting their initial competitive advantages. Second, LCF learn new technology by allocating Research and Development (R&D) fund and building research facilities. Third, LCF increase their competitiveness by leveraging their linkages and learning efforts. LCFs’ leverage activities are in forms of leapfrogging, developing new products with MNC, and entering new market by exploiting every opportunity. Besides, LCFs are helped by their government through three kinds of supports. First, governments give LCFs that fulfill governments’ requirements privileges. Second, governments reduce business risks faced by LCF by buying LCFs’ products, giving subsidies, and initiating basic research. Third, governments conduct cooperation with LCF through public research institutions for stimulating innovation.